Machining Study of TI-6AL-4V Using PVD Coated TiAlN Inserts - Andriya, Narasimhulu; Venkateswara Rao, P.; Ghosh, Sudarsan (Asian Review of Mechanical Engineering, 2012)
This paper deals with machining Ti6Al4V material. The experimental analysis was carried out using Response Surface Methodology (RSM). The detailed experiments under wet and dry conditions using the PVD coated TiAlN tools. In the present work the relationship of Ti6Al4V’s surface roughness and cutting forces with critical machining parameters and conditions, based on experimental input and output data, has been derived during the turning operation. It has been found through design of experiments technique that linear model is best fitted for predicting feed force and surface roughness under both dry and wet cutting environment. Linear model is also fitted for thrust force prediction during dry cutting. However under wet cutting condition a quadratic model is more suited for prediction of the thrust force. 2FI (2 Factor Interaction) model is found to be fitted for cutting force prediction under both the cutting environment.